Effect of cerium and lanthanum additives on plasma electrolytic oxidation of AZ31 magnesium alloy - 沈德久 马豪杰 郭长虹 蔡景瑞 李国龙 何东磊 杨庆祥 (Journal of rare earths, 2013)
Plasma electrolytic oxidation（PEO） coatings on AZ31 magnesium（Mg） alloy were developed using the aqueous solution with alkaline silicate and sodium hydroxide as a base electrolyte system.The effects of cerium（Ce） nitrate and lanthanum（La） nitrate additives on the voltage response,microstructure,compositions and corrosion resistance of PEO coatings were investigated by scanning electron microscopy（SEM）,energy-dispersive spectrum（EDS）,X-ray diffraction（XRD） and potentiodynamic polarization tests,etc.The results showed that Ce and La additives increased the stable voltage and compactness of the PEO coatings,while,those did not change the compositions of the PEO coatings.The corrosion resistance of the PEO coating obtained in solutions with La nitrate of 0.1 g/L was the best,followed by that with Ce nitrate of 0.1 g/L and that without additives.